'All is pure for the pure’: redefining purity and defilement in early Greek Christianity, from Paul to Origen - Blidstein, M (2014)
This thesis examines the meanings of purification practices and purity concepts in early Christian culture, as they were articulated and formed by Greek Christian authors of the first three centuries, from Paul to Origen. As purity and defilement are especially suited for articulating difference, hierarchy and change, these concepts were essential for early Christians, shaping their understanding of human nature, sin, history, and ritual. In parallel, the major Christian practices embodying difference and change, baptism, abstinence from food or sexual activity, were all understood, emoted and shaped as instances of purification. Two broad motivations, at some tension with each other, were at the basis of Christian purity discourse. The first was a substantive motivation: the creation and maintenance of anthropologies and ritual theories coherent with the theological principles of the new religion, and the integration of purity traditions and concepts into these worldviews and theories. The second was a polemic motivation: construction of Christian identity by laying claim to true purity while marking the purity practices and beliefs of others (Jews, pagan or “heretics”) as false. I trace the interplay of these factors through a close reading of second- and third-century Christian Greek authors discussing food abstentions, death defilement, sexuality and baptism, on the background of Greco-Roman and Jewish purity discourses. This thesis demonstrates three central arguments. First, purity and defilement are central concepts for understanding Christian cultures of the second and third centuries. Second, Christianities developed their own conceptions and practices of purity and purification, distinct from those current in contemporary and earlier Jewish and pagan cultures, though decisively influenced by them. Third, concepts and practices of purity and defilement were shifting and contentious, an arena for boundary-marking between Christians and others and between different Christian groups.